Effect of High Altitude on the Survival of COVID-19 Patients in Intensive Care Unit: A Cohort Study. (September 2022) - Jibaja, Manuel; Roldan-Vasquez, Estefania; Rello, Jordi; Shen, Hua; Maldonado, Nelson; Grunauer, Michelle; Díaz, Ana María; García, Fernanda; Ramírez, Vanessa; Sánchez, Hernán; Barberán, José Luis; Paredes, Juan Pablo; et al.
Purpose: The effect of high altitude ( ≥ 1500 m) and its potential association with mortality by COVID-19 remains controversial. We assessed the effect of high altitude on the survival/discharge of COVID-19 patients requiring intensive care unit (ICU) admission for mechanical ventilation compared to individuals treated at sea level.Methods: A retrospective cohort multi-center study of consecutive adults patients with a positive RT-PCR test for COVID-19 who were mechanically ventilated between March and November 2020. Data were collected from two sea-level hospitals and four high-altitude hospitals in Ecuador. The primary outcome was ICU and hospital survival/discharge. Survival analysis was conducted using semi-parametric Cox proportional hazards models.Results: Of the study population (n = 670), 35.2% were female with a mean age of 58.3 ± 12.6 years. On admission, high-altitude patients were more likely to be younger (57.2 vs. 60.5 years old), presented with less comorbidities such as hypertension (25.9% vs. 54.9% with p -value <.001) and diabetes mellitus (20.5% vs. 37.2% with p -value <.001), less probability of having a capillary refill time > 3 sec (13.7% vs. 30.1%, p -value <.001), and less severity-of-illness condition (APACHE II score, 17.5 ± 8.1 vs. 20 ± 8.2, p  < .01). After adjusting for key confounders high altitude is associated with significant higher probabilities of ICU survival/discharge (HR: 1.74 [95% CI: 1.46-2.08]) and hospital survival/discharge (HR: 1.35 [95% CI: 1.18-1.55]) than patients treated at sea level.Conclusions: Patients treated at high altitude at any time point during the study period were 74% more likely to experience ICU survival/discharge and 35% more likely to experience hospital survival/discharge than to the sea-level group. Possible reasons for these findings are genetic and physiological adaptations due to exposure to chronic hypoxia.